The triumph of God over evil : theodicy for a world of suffering - Hasker, William, 1935- (2008)
"Noted philosopher William Hasker explores a full range of issues concerning the problem of evil. Having taken account of the current state of the discussion and squarely facing some of the most trenchant arguments concerning evil marshaled by John K. Roth, D. Z. Phillips and others, Hasker forges a constructive in-depth response, showing why the evil in the world does not provide evidence of a moral fault in God, the world's creator and governor." --Book Jacket.
What Is the State of Play? -- Does Auschwitz Change Everything? -- Are God and Evil Compatible? -- Can We Understand Creation? -- Is the World Cruel? -- Why Is Life So Hard? -- Shouldn't God Be Doing More? -- Can God Triumph over Evil?
Includes bibliographical references and index.
Keywords: Theodicy; Good and evil